Texas High Schools and New Teachers: A Multi-Year Statewide Study - Cynthia Martinez-Garcia; John R Slate (Arizona State University, 2010)
We examined the five most recent years of data (2003-2004 through 2007-2008) from the Texas Academic Excellence Indicator System regarding new teachers employed at high school campuses. We specifically focused on the extent to which differences were present between high school campuses with the highest new teacher percentages and high school campuses with the lowest new teacher percentages. High school campuses with the highest new teacher percentages had higher percentages of minority students and higher percentages of economically disadvantaged students but lower percentages of at-risk students than did high school campuses with the lowest percentages of new teachers. Implications of these findings and suggestions for further research are discussed.